The Relationship between Early Mobilization with Post Intensity of Post Caesar Section Patients - Lesli Lesli; Putria Carolina; Suryagustina Suryagustina; Lidia Widia (Budapest International Research and Critics University, 2023)
Sectio Caesarea is an artificial birth where the fetus is born through an incision in the abdomen. The incision wound has an impact on the mother and the most felt impact is acute pain. Pain is a personal experience that is expressed differently in each individual. One of the non-pharmacological therapies to reduce pain is early mobilization. This study aims to determine the relationship between early mobilization and pain intensity in postoperative sectio caeserea patients in the Bougenville room of Primaya Betang Pambelum Hospital. This study used a correlational design with a cross sectional design and accidental sampling technique. Respondents in this study amounted to 37 respondents who met the inclusion criteria. Data collection used an observation sheet which was then analyzed using the Rank Spearman statistical test. The results of statistical analysis revealed that early mobilization was in the good category and the respondent's pain intensity was in the fully decreased category with p value = 0.000 (p <0.05). There is a relationship between early mobilization and pain intensity in post SC patients as evidenced by the results of p <α with a significant level of 0.05 indicating a significant and significant relationship between early mobilization and pain intensity.